Visceral Data for Dance Histories: Katherine Dunham's People, Places, and Pieces. Issue 1 (March 2022) - Bench, Harmony; Elswit, Kate
Abstract : Between 1947 and 1960, choreographer Katherine Dunham spent over 5, 000 days in hundreds of cities on six continents. During that time, almost 200 dancers, drummers, and singers traveled with her, performing 166 repertory pieces. Dunham's expansive work lends itself to digital approaches that illuminate the complex ways history is iterated across bodies, and how the specific questions raised by dance history underpin a visceral approach to the digital humanities.